Effect of Prophylactic Intrathecal Pethidine on the Incidence of Shivering on Mothers Undergoing Cesarean Section Under Spinal Anesthesia: A Randomized Controlled Trial - Girma, Timsel; Alemu, Wagaye; Assen, Sofia (Frontiers in Medicine, 2022)
Background- Shivering is the most common & unpleasant complication of anesthesia with an incidence of 70.7% in cesarean section done under Spinal anesthesia which is associated with cardiovascular & respiratory complications. Shivering increases metabolic rate by 600%, intracranial & intraocular pressure, production of carbon dioxide & lactic acidosis, as well as it also increases the risk of a floating clot, postoperative bleeding, delayed wound healing, and uncomfortable recovery time due to pain. Even though it causes such devastating complications; prevention of shivering is not well investigated. This study aimed to assess the effect of Intrathecal Pethidine on the Incidence & Severity of Shivering in patients undergoing Cesarean section under Spinal anesthesia Methods- After Obtaining Ethical clearance from IRB, a Randomized controlled trial was conducted in a total of 86 pregnant mother who was randomly allocated into two groups by computer-generated random number.1ml of 10mg preservative-free pethidine was added to 12.5mg of 0.5% bupivacaine for spinal anesthesia in treatment group & 12.5mg of 0.5% bupivacaine alone was given in control group. Vital signs, incidence & severity of shivering as well as adverse effect were recorded intraoperatively, in PACU & the ward. Data were analyzed by SPSS version 25. Independent sample t-test and Mann Whitney U test were used for continuous variables by considering the assumption. Categorical data were analyzed with Chi-square. A P-value less than 0.05 were considered statistically significant. Result- A total of 86 patients' data were analyzed and the result shows that the incidence of shivering was 53.5% in the control group and 20.9% in the treatment group which was statistically significant with p=0.002. The intensity of shivering was also higher in the control group than the treatment group with p=0.004. considering an adverse effect, the incidence of pruritus was 18.6% in the treatment group while none of the control got pruritus; which was statistically significant with p=0.003. But the incidence of PONV was not significantly different with p>0.005. Conclusion- administration of 10mg of pethidine intrathecally during spinal anesthesia is effective in reducing incidence and severity of shivering without causing significant adverse effects. Trial ID: PACTR202110617970132 https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=17179 Keywords: pethidine